ECOLOGICAL CONSCIOUSNESS AND PEDAGOGICAL RESPONSIBILITY: INNOVATIVE APPROACHES IN EDUCATION FOR SUSTAINABLE DEVELOPMENT - Mamdaliyev Foziljon Abdullaevich; Sattorova Dilfuzakhon Kurbonalievna; Khamidova Zulkhumor Shukhratjon qizi; Ghoibnazarova Mukhayyokhon Abdusamadovna; Razakov Bakhtiyorjon Murotovich; Otakhonova Mavjudakhon Alijon qizi (Ecominds Press, 2025)
The article provides a scientific analysis of the theoretical and practical foundations of the harmony between ecological consciousness and pedagogical responsibility. The author introduces innovative pedagogical models such as the Theory of Ecological Resonance, EcoPedagogical Spiral, Pedagogic EcoMatrix, and Green Campus Culture. The study highlights the role of environmental education in sustainable development, the integration of national and international experiences, and the application of digital technologies in ecological learning. As a result, a new educational paradigm — Ecopedagogy of Sustainable Development — is proposed, synthesizing science, ethics, and spirituality. The findings have significant practical value for developing ecological competence, environmental responsibility, and “green thinking” among students and educators within the education system.
Keywords: Ecological consciousness, pedagogical responsibility, sustainable development, innovative education, ecopedagogy, ecological culture, green campus.